The Place of Earth in Lutheran Funeral Rites: Mapping the Current Terrain - Stewart, Benjamin M. ca. 21. Jh. (Dialog, 2014)
Do funeral rites help Christians leave the earth or return to the earth? This article identifies the conceptual metaphors by which the funeral rites in Evangelical Lutheran Worship portray earth. All of the conceptual metaphors related to earth in the rites identified by this essay are at least compatible with an overarching image of journey, and most of the conceptual metaphors are directly structured by the journey image. While these conceptual metaphors can be understood as mapping a journey that seeks to abandon the earth for an otherworldly heaven, a number of tensions within the metaphors challenge this trajectory with an earthward goal of resting in the fruitful, living earth. The article concludes by briefly identifying some ecotheologically promising synergies between some of the biblical-theological images and the emerging practices of conservation burial.